Optimizing Total Hip and Knee Arthroplasty Among an Underserved Population: Lessons Learned From a Quality-Improvement Initiative - Mouhanad M. El-Othmani, MD; Kyle McCormick, MD; Winnie Xu, BA; Thomas Hickernell, MD; Nana O. Sarpong, MD, MBA; Wakenda Tyler, MD, MPH; Carl L. Herndon, MD (Arthroplasty Today, 2024)
Background: Under-represented minorities and those with noncommercial insurance have higher medical comorbidities and complications following elective total joint arthroplasty (TJA). In an effort to bridge this gap, our center implemented a preoperative optimization protocol for TJA in a Medicaid Clinic (Clinic). The purpose of this study is to assess the effectiveness of that protocol and highlight challenges associated with caring for this patient population. Methods: This retrospective analysis included 117 patients undergoing TJA between January 2015 and January 2020. In 2015, the protocol was implemented as a mandatory practice prior to TJA. A contemporary control cohort from the private office was also analyzed. Patient demographics, American Society of Anesthesiologists score, and postoperative complications were collected. Results: Within the clinic group, 52.5% (62) patients identified as Hispanic with 46.6% (55) Spanish-speaking as primary language, compared to 9.3% (11) and 8.5% (10) in the office group (P = .0001), respectively. Clinic group patients were significantly more likely to experience a complication compared to office patients (20 vs 7, respectively). There was no difference in complication or reoperation rate between clinic patients who underwent the optimization protocol and those who did not. Conclusions: The findings from this study highlight the demographic and comorbidities profile of an underserved population, and report on results of a quality improvement initiative among that population, which failed to improve postoperative outcomes. These results underscore the need for further study in this population to improve outcomes and health equity.